PENGARUH NET WORKING CAPITAL, DIVIDEND PAYMENT, CASH CONVERSION CYCLE, DAN OPERATING CASH FLOW TERHADAP CASH HOLDING PERUSAHAAN - INDRA PRASETYO, LAXMANA (Jurnal Akuntansi AKUNESA, 2017)
Retaining cash in the optimal point is very important towards the continuation of an organization or a company. In some articles mentioned that